Autophagy modulation in mammarenavirus infection - Gallo, Giovanna Lucrecia (2021)
Mammarenavirus genus groups viruses causing human haemorrhagicdiseases, including the New World (NW) Junín virus (JUNV), and the Old World(OW) viruses Lassa (LASV), among others. The high mortality and morbidityrates associated to pathogenic mammarenaviruses, the absence of vaccinesand the constant threat of new emerging species, make these viruses a publichealth concern in endemic areas. Autophagy is a widely-known intracellularmetabolic pathway involved in maintaining the cellular homeostasis inresponse to several stress conditions.